Pemikiran Pendidikan Islam dalam Persfektif Ibnu Sina - Wely dozan (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2019)
This paper tries to discuss the views of Ibn Sina in Islamic education and its relevance in modern education today. The concept of education according to Ibn Sina aims to develop all the potential possessed by someone towards a perfect direction, namely physical, intellectual and moral development. In addition, the purpose of education must be directed at efforts to prepare someone to be able to live in the community together by doing the work or skills chosen in accordance with their talents, readiness, tendencies and potential. These assumptions caused Ibn Sina to reconstruct and provide a new direction of thinking to develop a better and better quality education. In short, this paper will trace the philosophical meaning in Ibn Sina's thoughts on education through philosophical bases of thought.